ANALISIS ERGONOMI BEBAN KERJA MENTAL DAN FISIK TERHADAP PENGENDARA OJEK ONLINE WANITA TERHADAP DIHAPUSNYA PROGRAM LADY GRAB - Oktavera, Isnia; Widodo, Lamto; Ahmad (Jurnal Mitra Teknik Industri, 2024)
Online motorcycle taxis or commonly referred to as ojols are motorbike taxis that can be ordered via a mobile phone that uses the internet by using an application. As time goes by, online motorcycle taxis in Indonesia have many choices and competitors that have sprung up by creating online motorcycle taxi applications that have advantages in their respective companies. This research aims to analyze the workload experienced and identify the causes of excessive workload felt by female online motorcycle taxi drivers. The research subjects this time were 31 female grab drivers in the cities of Tangerang and Jakarta. The measured workload is physical and mental workload. The benefits of this research are to find out how much the level of workload, both physical and mental, is experienced by female online motorcycle taxi drivers and to find out whether the number of workers is in accordance with the optimal standard of the driver's workload. The purpose of conducting this research is to analyze what kind of mental workload is experienced by female online motorcycle taxi drivers during the abolition of the lady grab program. Measurement of mental workload is carried out by the mental workload measurement method used, namely; NASA-TLX, Nordic Body Map, and RSME (Rating Scale Mental Effort). The calculation result of 79.5 shows the average score borne by female online motorcycle taxi drivers in the high and very high categories. The results of the RSME calculation give an average score of 968.6 with a description of a very heavy mental workload.